Manajemen Konseling Dalam Mengantisipasi Bullying Bagi Pelajar di Sekolah - Dwi Novriyansah, M. Anasrul; Eka Saputra, Darwin; Wigati, Indah; Yuniar (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This research is motivated by the increasing cases of bullying occurring in Indonesia, especially in educational institutions. It is known that Indonesia ranks fifth out of 78 countries in bullying cases. The method used is qualitative descriptive with a case study design. In this study, researchers used literature review with a literature review perspective, creating a complex overview, examining detailed reports from the respondents' point of view, and conducting studies in situational settings. Data collection in this research was carried out through the examination of several sources including journal articles, documents, and other teaching materials. This method involves the identification, selection, analysis, and synthesis of literature relevant to the research topic. Based on the results and discussion, it is necessary to have counseling management to anticipate bullying among students in schools. Bullying encompasses various actions aimed at harming others both physically and mentally. There are several types of bullying, namely physical bullying, which involves physical contact such as hitting; verbal bullying, which involves using inappropriate words towards the victim; social bullying, which can result in the deterioration of the victim's reputation; and cyberbullying, which utilizes technology to carry out bullying actions. The main causes of bullying behavior stem from family, peer influence, and media influence, including television programs and smartphones displaying violent scenes.